Iron and zinc-modified nano-biochar alleviate salinity stress in paddy soil by modulating nutrient availability and microbial communities - Shah, Asad; Sultan, Haider; Khan, Mohammad Nauman; Ali, Waqar; Abbas, Hafiz Muhammad Mazhar; Khan, Muhammad Numan; Ye, Tao; Nie, Lixiao (Frontiers in Microbiology, 2026)
IntroductionSoil salinization is a major constraint to agricultural productivity on Hainan Island, China, as it reduces soil fertility and disrupts microbial community structure. Nano-modified biochar has emerged as a promising strategy to improve soil quality and microbial resilience under saline conditions. This study evaluated the effects of iron- and zinc-modified nano-biochar on soil physicochemical properties and microbial communities in saline and non-saline paddy soils.MethodsA pot experiment was conducted using four treatments: control (CK), pristine biochar (BC), iron-modified biochar (FeBC), and zinc-modified biochar (ZnBC). Soil physicochemical properties, enzyme activities, microbial biomass, and bacterial and fungal community composition were analyzed using standard chemical assays and high-throughput sequencing techniques.ResultsApplication of nano-modified biochar significantly increased soil organic matter, soil organic carbon, and the availability of macronutrients (N, P, and K). FeBC and ZnBC enhanced microbial biomass carbon and nitrogen as well as urease and β-glycosidase activities in saline soil. Nano-biochar treatments altered microbial community composition, increasing the abundance of salt-tolerant bacterial phyla such as Proteobacteria, Chloroflexi, and Bacteroidota under saline conditions, while modifying fungal community structure, including increased relative abundance of Chytridiomycota under FeBC treatment.